EMPLOYING MIND MAPPING TECHNIQUE TO FACILITATE SECONDARY SCHOOL STUDENT TO WRITE NARRATIVE TEXT AT THE FIRST GRADE IN THE 2020/2021 ACADEMIC YEAR - Siti Maysaroh (Journal of English Teaching and Learning, 2021)
Employing Mind Mapping Technique to Facilitate Secondary School Student to Write Narrative Text At The First Grade In the 2020/2021 Academic Year. This research was conducted on class XI students of SMA Negeri 1 Wongsorejo Banyuwangi. This research used Class Action Research with research design using Pre-Test and Post-Test in cycle 1 and cycle 2. The data of this study were in the form of student scores both pre-test and post-test. The data collection technique was carried out by researchers by collecting student scores, observation sheets on student activities both before research, and after research, interviews with students and teachers on learning before and after using the mind mapping method. The results showed that: learning using the mind mapping method was classified as very supportive of students' abilities in learning writing narrative text. This is evidenced by the increase in student test results from cycle 1 with an average result of 72.79 students with a completeness level of 59%, increasing in cycle 2 with an average value of 79.26 with a completeness level reaching 85%. Student responses to learning using the mind mapping method are very happy, and students are quite active in group learning activities. In cycle 1 students do individual learning activities but the results are still not optimal because students still do not understand the mind mapping method, but in cycle 2 with group learning students experience an increase in ability because students can discuss with their group friends.